Perbedaan Hasil Belajar Pengetahuan IPA Siswa Antara Model Discovery Learning dengan Pembelajaran Konvensiona - Lusia, Martha; Silvinia, Sivinia; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research has purpose to knowing the significant differences in cognitive learning outcomes student of Science Between Model Discovery learning with Conventional Learning. This type of research is a quasi experiment research with two-group posttest-only design. The sample in this research is class VA and VB SDN 07 Teladan. Technique data collection using test. Test the hypothesis in this study using the formula t-test. Based on the results showed that the average of the Discovery learning’s class was 85,3  and the Conventional Learning’s class average was 72,1. Based on the calculation of t test (t-test) on posttest obtained tcount (6,38) >  ttable (1,66). This means that there is an differences in cognitive learning outcomes student of Science Between Model Discovery learning with Conventional Learning. Keyword : Learning Outcomes of Science, Model Discovery learning, Conventional Learning